2014
DOI: 10.2214/ajr.13.11812
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Image Processing on the Detection of Cancers in Digital Mammography

Abstract: OBJECTIVE. The objective of our study was to investigate the effect of image processing on the detection of cancers in digital mammography images. MATERIALS AND METHODS. Two hundred seventy pairs of breast images (both breasts, one view) were collected from eight systems using Hologic amorphous selenium detectors: 80 image pairs showed breasts containing subtle malignant masses; 30 image pairs, biopsy-proven benign lesions; 80 image pairs, simulated calcification clusters; and 80 image pairs, no cancer (normal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 20 publications
1
22
0
Order By: Relevance
“…This type of analysis has been performed previously in such similar studies. 8,9,14 Observer's marks were classified as either true positives or false positives. Each mark was compared to the rectangular box draw around the cancers by the experienced radiologist.…”
Section: Discussionmentioning
confidence: 99%
“…This type of analysis has been performed previously in such similar studies. 8,9,14 Observer's marks were classified as either true positives or false positives. Each mark was compared to the rectangular box draw around the cancers by the experienced radiologist.…”
Section: Discussionmentioning
confidence: 99%
“…This processing was designed to be appropriate for a wide range of image qualities but it may not have been perfectly adapted for each type of detector in the trial. Research into the impact of different types of image processing on cancer detection has so far indicated that it has a small effect on calcification detection but little effect on the detection of non-calcification malignant lesions [27,28]. …”
Section: Discussionmentioning
confidence: 99%
“…Alphabetical order is not random, but it should effectively mix together the images with and without meniscal tears as there is no association between the first few letters of a patient’s name and the likelihood that the patient will have a meniscal tear 15 . If the authors asserted a method to be random, the method was recorded as random, even if some constraints to random ordering were specified 16 …”
Section: Methodsmentioning
confidence: 99%